Private monitoring and communication in the repeated prisoner's dilemma - Yu Awaya (Games, 2021)
This paper provides a model of the repeated prisoner's dilemma in which cheap-talk communication is necessary in order to achieve cooperative outcomes in a long-term relationship. The model is one of complete information. I consider a continuous time repeated prisoner's dilemma game where informative signals about another player's past actions arrive following a Poisson process; actions have to be held fixed for a certain time. I assume that signals are privately observed by players. I consider an environment where signals are noisy, and the correlation of signals is higher if both players cooperate. We show that, provided that players can change their actions arbitrary frequently, there exists an equilibrium with communication that strictly Pareto-dominates all equilibria without communication.
Keywords: 330; communication; private monitoring; repeated games